2019
DOI: 10.21203/rs.2.17871/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors influencing the sustained utilization of child welfare services among children 18 to 59 months in a low-income rural community.

Abstract: Background: Despite substantial progress in reducing child mortality, concerted efforts remain necessary to avoid preventable deaths in children under-5 years and to accelerate progress in improving child survival further. The patronage of child welfare services therefore remains paramount to the attainment of these goals. This study identified the factors that influence the patronage of child welfare services in a rural community in the Ho West District of the Volta region. Methodology: The study employed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(21 reference statements)
0
1
1
Order By: Relevance
“…Furthermore, a study conducted during the COVID-19 era aimed to determine personal and job-related characteristics among health workers recruited from public hospitals in Accra. The prevalence of burnout among the participants was relatively lower (20.57%) than what is being reported in this present study [23]. Overall, these ndings highlight the signi cant issue of burnout among nurses and midwives in the selected CHAG facilities.…”
Section: Discussioncontrasting
confidence: 62%
“…Furthermore, a study conducted during the COVID-19 era aimed to determine personal and job-related characteristics among health workers recruited from public hospitals in Accra. The prevalence of burnout among the participants was relatively lower (20.57%) than what is being reported in this present study [23]. Overall, these ndings highlight the signi cant issue of burnout among nurses and midwives in the selected CHAG facilities.…”
Section: Discussioncontrasting
confidence: 62%
“…Meanwhile, a preprint published by Konlan et al [25] revealed that children of married caregivers were more likely to complete the CWC schedule, even after completion of the immunization schedule, in rural parts of Tamale, Northern Ghana, compared to children of unmarried caregivers. With our study participants sharing similar socio-geographical and economic characteristics as those of Konlan et al [25], it could be assumed that children of married women in the Garu-Tempane District of Northern Ghana are more likely to attend and complete the CWC schedule, even after completion of the immunization schedule. Our finding, therefore, adds to build knowledge on the role of marriage in child health growth promotion and monitoring in Northern Ghana.…”
Section: Discussionmentioning
confidence: 99%